INVESTIGATING RELIGIOUS BOARDING SCHOOL SEMINARIANS’ SELF-EFFICACY IN ACADEMIC READING ABILITY - Mahardika, Agustine Andriana Ayu (ELTR Journal, 2025)
Reading becomes a crucial skill to have in this digital era. People can analyze and acknowledge the content of the text by engaging their critical thinking to obtain useful knowledge that may be beneficial for their future endeavors. High self-efficacy is important to be implemented to test out students’ ability in academic reading. This research aimed to investigate religious boarding school seminarians’ self-efficacy in academic reading ability. A Likert scale, consisting of 10 items of statements, was distributed to 36 third-year seminarians and an in-depth interview was done with two third-year seminarians. TKT 3 is applied and it aims to show the concept (proof-of-concept) of crucial purpose and/or features analytically and experimentally. The findings revealed that religious boarding school seminarians tend to find solutions to their problems in finishing academic reading tasks. Future researchers who are interested in broadening the topic are recommended to do research involving more religious boarding schools to deepen the data and improve the trustworthiness of the data.